Commentary on the semi-sentence in the book Al-Tanbih on the explanation of the problems of Al-Hamasa by Ibn Jinni Analytical study (Damascus University Journal of arts and humanities sciences, 2026)
The research deals with the phenomenon of suspending the quasi-sentence through analysis and grammatical study, trying to clarify this grammatical term and explain its precise meaning, especially since this term was not explained adequately by the predecessors, although it is common in their books. However, they used it a lot in their speech without clarifying its true nature, and without dedicating an independent chapter to it in their books. The research studies this phenomenon theoretically, and explains the reason for the specialization of quasi-sentences in suspension and not others.Then the research studies this phenomenon with an applied study in the book Al-Tanbih ala Sharh Mushkilat Al-Hamasa by Abu Al-Fath Othman bin Jinni (392 AH), showing the most important foundations he relies on in his treatment of this phenomenon, and tries to clarify the features of his doctrine in suspending the quasi-sentence. The research sheds light on Ibn Jinni's approach to commenting on quasi-sentences, how he dealt with the duality of (meaning and craft), and how he combined them together and took into account the meaning and followed it while preserving the craft and protecting its origins.The research also showed Ibn Jinni's opinions and uniqueness in this regard, and his influence by scholars who preceded him..
Keywords: Alert; Comment; Quasi-sentence; Adverb; Preposition and noun; Agent; Ibn Jinni; grammatical grounding